Evaluación técnico-financiera de la inyección de agua en un campo de la Cuenca del Catatumbo colombiano mediante simulación analítica (2018)
The studied Field was discovered in the 1940s, although its exploitation began in 1945. It is located in the northeast of Colombia in the department of Norte de Santander, and is also part of the Catatumbo Basin. The geological model of the field was updated with the files found in the database of the company ECOPETROL S.A. This process included the compilation and organization of the available information on production and petrophysics of the field, in addition to including the reports of drilling, completion, injection records, workovers and other information available for each of the wells. From the definition of each of the basic concepts required to carry out the process of water injection and selective water injection, the tools available to the SAHARA software are described, as well as the way in which the analytical simulation will be carried out, which will use the segregated flow method to develop each of the injection and production predictions necessary for the development of the project. Finally, a financial analysis will be carried out to evaluate the costs and revenues generated during the implementation of the project, as well as to evaluate the feasibility of implementation and the profitability of the project for a period of 30 years.